Gendered patterns in students' motivation profiles regarding iSTEM and STEM test scores: a cluster analysis - Seppe Hermans; Marijn Gijsen; Tine Mombaers; Peter van Petegem (SpringerOpen, 2022)
Abstract Background Promoting and improving STEM education is being driven by economic concerns as modern economies have a rising demand for qualified researchers, technicians, and other STEM professionals. In addition, women remain under-represented in STEM-related fields, with significant economic and societal consequences. Abundant research has shown that gendered pathways into and away from STEM are mediated through motivation, but there is paucity of knowledge regarding gendered patterns in high school students' motivation profiles, especially in transdisciplinary domains like integrated STEM (iSTEM). This study addresses these gaps by examining the interconnection between patterns in motivation profiles towards integrated STEM (iSTEM), gender and STEM test scores. Results Using cluster analysis in a sample of N = 755 eighth grade students, we established four distinct motivation profiles. Subsequently, a multinomial logistic regression was performed to calculate predicted probabilities for cluster membership based on gender and test scores. Cluster distributions indicate significant differences based on gender and test score. Although our analysis shows no difference in average test scores, significant gender differences can be found in and between motivation profiles. For instance, girls are more likely to belong to a less favorable profile cluster than boys. In that cluster, girls have on average a significantly higher test score compared to boys, indicating a differential effect of motivation profiles. Conclusions The concept of motivational co-expression emphasizes a need for instructors to move past the simple high or low motivation labels, and toward an appraisal that recognizes how students adopt a complex interplay of motivation types. Moreover, the gender analyses raise questions about how we can move towards more equitable approaches.